Deterioration of visuospatial associative memory following a first psychotic episode: a long-term follow-up study. Issue 1 (19th June 2017) - Wannan, C. M. J.; Bartholomeusz, C. F.; Cropley, V. L.; Van Rheenen, T. E.; Panayiotou, A.; Brewer, W. J.; Proffitt, T. M.; Henry, L.; Harris, M. G.; Velakoulis, D.; McGorry, P.; Pantelis, C.; et al.
Abstract : Background: Cognitive deficits are a core feature of schizophrenia, and impairments in most domains are thought to be stable over the course of the illness. However, cross-sectional evidence indicates that some areas of cognition, such as visuospatial associative memory, may be preserved in the early stages of psychosis, but become impaired in later established illness stages. This longitudinal study investigated change in visuospatial and verbal associative memory following psychosis onset. Methods: In total 95 first-episode psychosis (FEP) patients and 63 healthy controls (HC) were assessed on neuropsychological tests at baseline, with 38 FEP and 22 HCs returning for follow-up assessment at 5–11 years. Visuospatial associative memory was assessed using the Cambridge Neuropsychological Test Automated Battery Visuospatial Paired-Associate Learning task, and verbal associative memory was assessed using Verbal Paired Associates subtest of the Wechsler Memory Scale - Revised. Results: Visuospatial and verbal associative memory at baseline did not differ significantly between FEP patients and HCs. However, over follow-up, visuospatial associative memory deteriorated significantly for the FEP group, relative to healthy individuals. Conversely, verbal associative memory improved to a similar degree observed in HCs. In the FEP cohort, visuospatial (but not verbal) associative memory ability at baseline was associated with functional outcome at follow-up. Conclusions: Areas of cognition that develop prior to psychosis onset, such as visuospatial and verbal associative memory, may be preserved early in the illness. Later deterioration in visuospatial memory ability may relate to progressive structural and functional brain abnormalities that occurs following psychosis onset.